Membranas densas e porosas obtidas a partir de alginato e quitosana incorporadas com sinvastatina para atuar como curativo bioativo de feridas da pele. - Monteiro, Rubens Teles (2023)
Recently, many studies have been developed in the search for dressings that have the capacity to modulate the release of drugs, as traditional dressings (gauze, cotton, bandages, among others) are not efficient in healing complex wounds. The present work produced five different membranes for the sustained administration of simvastatin, differentiating them by the number of layers (mono or bilayer), the polymer used (alginate or chitosan) and the porosity (dense or porous). The different porosities were prepared by two drying processes, evaporation of the solvent by convection and freeze-drying. The membranes were characterized through physicochemical, thermal, morphological and mechanical analyses. Simvastatin was used because it has an anti-inflammatory effect, its release was studied using Franz diffusion cells and the stability of the drug in the membrane in relation to time was also evaluated. The cytotoxicity of the membranes was evaluated using fibroblast and keratinocyte cells. The results showed that the different drying processes, the number of layers and the use of different polymers directly interfered in the morphological characteristics and physical-chemical properties, providing each of the five membranes with distinct characteristics. Porous membranes proved to be more appropriate for wounds with greater exudate production, while dense membranes for wounds in parts of the body with greater movement. The in vitro release study showed that bilayer membranes can sustain a longer release of the drug than the monolayer membrane, which can benefit from reducing dressing changes. The results of the storage study showed that after 6 months, all membranes maintained around 98 % of the initial drug content, and also without changing their visual appearance. The antimicrobial activity test showed that the chitosan membrane, despite lower moisture absorption than alginate membranes, has bacteriostatic activity, thus being suitable for infected wounds and the cell viability test found that the membranes produced are not cytotoxic. Therefore, all membranes studied showed promising characteristics for use in the treatment of different types of skin lesions, such as superficial or deep, acute or chronic, infected and in different locations on the skin.